Self-Reported Executive Functioning in Everyday Life in Parkinson’s Disease after Three Months of Subthalamic Deep Brain Stimulation - Uyen Ha Gia Pham; Stein Andersson; Mathias Toft; Are Hugo Pripp; Ane Eidahl Konglund; Espen Dietrichs; Ulrik Fredrik Malt; Inger Marie Skogseid; Ira Ronit Hebolt Haraldsen; Anne-Kristin Solbakk (Parkinson's Disease)
Objective. Studies on the effect of subthalamic deep brain stimulation (STN-DBS) on executive functioning in Parkinson’s disease (PD) are still controversial. In this study we compared self-reported daily executive functioning in PD patients before and after three months of STN-DBS. We also examined whether executive functioning in everyday life was associated with motor symptoms, apathy, and psychiatric symptoms. Method. 40 PD patients were examined with the Behavior Rating Inventory of Executive Function-Adult Version (BRIEF-A), the Symptom Checklist 90-Revised (SCL-90-R), and the Apathy Evaluation Scale (AES-S). Results. PD patients reported significant improvement in daily life executive functioning after 3 months of STN-DBS. Anxiety scores significantly declined, while other psychiatric symptoms remained unchanged. The improvement of self-reported executive functioning did not correlate with motor improvement after STN-DBS. Apathy scores remained unchanged after surgery. Only preoperative depressed mood had predictive value to the improvement of executive function and appears to prevent potentially favorable outcomes from STN-DBS on some aspects of executive function. Conclusion. PD patients being screened for STN-DBS surgery should be evaluated with regard to self-reported executive functioning. Depressive symptoms in presurgical PD patients should be treated. Complementary information about daily life executive functioning in PD patients might enhance further treatment planning of STN-DBS.